Utility of Laboratory Test Result Monitoring in Patients Taking Oral Terbinafine or Griseofulvin for Dermatophyte Infections - Stolmeier, Deirdre A. (JAMA Dermatol, 2018)
IMPORTANCE: Terbinafine hydrochloride and griseofulvin are effective oral treatments for dermatophyte infections but have been associated with hepatic and hematologic abnormalities. The prevalence of alanine aminotransferase elevations, aspartate aminotransferase elevations, anemia, lymphopenia, and neutropenia among adults and children taking terbinafine and griseofulvin is unclear. OBJECTIVE: To measure the rate of laboratory test result abnormalities in healthy adults and children taking terbinafine or griseofulvin for dermatophyte infections. DESIGN, SETTING, AND PARTICIPANTS: This retrospective study assessed adults and children taking terbinafine or griseofulvin for dermatophyte infections from January 1, 2006, to December 31, 2016. Data were collected from one Midwest health care system. Exclusion criteria were preceding diagnosis of hepatic or hematologic condition and preceding or concurrent use of oral ketoconazole, amphotericin, or itraconazole. MAIN OUTCOMES AND MEASURES: The rates of elevated alanine aminotransferase measurements, elevated aspartate aminotransferase measurements, anemia, lymphopenia, and neutropenia in adults and children taking terbinafine, griseofulvin microsize, or griseofulvin ultramicrosize were calculated. Secondary measures included rates of baseline abnormalities, frequency of laboratory test results that required additional testing or discontinued use of medication, and laboratory test result monitoring practices. RESULTS: This study included laboratory data from 4985 patients (mean [SD] age, 42.8 [20.3] years; 2288 [45.9%] female) receiving 4309 courses of terbinafine, 634 courses of griseofulvin microsize, and 159 courses of griseofulvin ultramicrosize. We identified a low rate of laboratory test result abnormalities in patients taking terbinafine or griseofulvin. When laboratory test result abnormalities occurred, most were low grade (212 [93.4%] grade 1) and did not require subsequent laboratory test result evaluation or discontinued use of medication (15 051 [99.9%]). Elevations in alanine aminotransferase measurements were detected infrequently and were comparable to baseline detection rates (61 [3.5%] vs 95 [3.6%] for terbinafine, 2 [2.1%] vs 3 [3.7%] for griseofulvin microsize, and 0 vs 2 [5.0%] for griseofulvin ultramicrosize). Rates of elevated aspartate aminotransferase measurements, anemia, lymphopenia, and neutropenia were also infrequent and comparable to baseline rates. CONCLUSIONS AND RELEVANCE: In this study. the rates of alanine aminotransferase elevations, aspartate aminotransferase elevations, anemia, lymphopenia, and neutropenia in adults and children taking terbinafine or griseofulvin were low and equivalent to the baseline rates of abnormalities in this population. Routine interval laboratory test result monitoring appears to be unnecessary in adults and children without underlying hepatic or hematologic conditions taking terbinafine or griseofulvin for dermatophyte infections. Abandoning frequent laboratory monitoring can decrease unnecessary health care spending, decrease patient psychological angst associated with blood draws, and allow for expanded use of these effective oral medications.